Español (Revista Electrónica Calidad en la Educación Superior, 2024)
This study describes the strengths and weaknesses in the reaccreditation process of SINAES in the Master's program in Education Administration (MAE) belonging to the postgraduate program in Educational Sciences at the University of Costa Rica (PPCEDU). To achieve this purpose, a non-experimental qualitative case study is conducted, and techniques such as documentary review and interviews with individuals directly involved in the program's reaccreditation process are used. The main findings highlight that the program has very relevant strengths to achieve reaccreditation, such as program continuity, a solid structure, teaching quality, the resources available at the University of Costa Rica in general, and sustainability to carry out the process. However, there are aspects that hinder accreditation and depend on adequate management and organization among the program, the Postgraduate Studies System (SEP), and the base unit of the School of Educational Administration (EAE).
Keywords: Accreditation; educational quality; self-evaluation; higher education